Um Pas de Deux da estratégia com a arte: as práticas da companhia de dança grupo Corpo - Ernani Viana Saraiva (2009)
This research aimed to build a strategy concept observing the practices developed by observing the managers and other memberspractices at a culture industry organization which operate at Brasils scenic arts sector. It is adopted the research stream which searches the comprehension of strategy as practice. The dance company Grupo Corpo is considered one of the best, perhaps the best one in the whole Brazilian territory and oneof the best in the world as well. Their success last since the company foundation in 1976, reason enough to justify choosing this organization as research locus. In order to attend the theoretical basis and the formulated questions, it was developed a qualitative research. An ethnography was done during eleven month by using field notes,photography, video and sound recording to collect data. There were formal and informal registers, using semi-structured interviews, spontaneous data collection with associates, executives, managers and other employees. The result was 214 recorded sound registers, 120 hours of video, 9,000 pictures taken from organizations operational quotidian and 3,000 documents digitalized. To construct analysis andinterpretation of collected data, an ethnographic register from spectacle construction was done together with situational analysis, a new Adele Clarkes grounded theory approach. As support tools, there were used the discourse analysis based on Norman Fairclough and Michel Foucaults works. To the data treatment, the Nvivo 8 softwarewas used which made possible dealing with raw sound and video records enriching the observed phenomena interpretation. To aim the proposed target, it was articulated theoretical arguments developed favorably and unfavorably to strategy as practice by several authors like Stewart Clegg, Paula Jarzabkowski and Richard Whittington, among others. There were used as well the strategy and tactics concept of Michel de Certeau and social area theories, the remarkable contributions of Peter L. Berger and Thomas Luckmann, with the Social Construction of Reality, Kenneth Gergens social constructionism and reality concept from William I. Thomas and Dorothy Thomas. As analysis result, it was presented a strategy concept discursively associated to identifiedpractices and the developed conceptual dimensions: future, paths, context and practices.